Comparison and functional characterisation of peripheral blood mononuclear cells isolated from filarial lymphoedema and endemic normals of a South Indian population. Issue 11 (20th September 2017) - Nathan, Abel Arul; Dixit, Madhulika; Babu, Subash; Balakrishnan, Anand Setty
Abstract: Objective: The underlying problem in lymphatic filariasis is irreversible swelling of the limbs (lymphoedema), which is a unique feature of lymphatic insufficiency. It is still unclear whether the natural ability of lymphatics to form functional lymphatic vasculature is achieved or attenuated in the lymphoedemal pathology. Clinical studies have clearly shown that circulating lymphatic progenitors (CLPs), a subset of bone marrow‐derived mononuclear cells (PBMCs), contribute to post‐natal lymph vasculogenesis. CLP‐based revascularisation could be a promising strategy to bypass the endothelial disruption and damage incurred by the filarial parasites. Thus our aim was to compare and characterise the functional prowess of PBMCs in physiological and lymphoedemal pathology. Methods: PBMCs were isolated from venous blood sample from drug‐naive endemic normals (EN) and drug‐deprived filarial lymphoedema (FL) individuals using density gradient centrifugation. Adhesion, transwell migration and in vitro matrigel assays were employed to characterise the lymphvasculogenic potential of PBMCs. CLPs were phenotypically characterised using flow cytometry; expression levels of lymphatic markers and inflammatory cytokines were quantified using qRT‐PCR and ELISA, respectively. Results: PBMCs from FL group display poor adherence to fibronectin ( P = 0.040), reduced migration towards SDF‐1 α ( P = 0.035), impaired tubular network ( P = 0.004) and branching point ( P = 0.048) formation. The PBMC mRNA expression of VEGFR3 ( P = 0.039) and podoplanin ( P = 0.050) was elevated, whereas integrin α 9 ( P = 0.046) was inhibited in FL individuals; additionally, the surface expression of CD34 ( P = 0.048) was significantly reduced in the FL group compared to the EN group. Conclusion: PBMCs from filarial lymphoedema show defective and dysregulated lymphvasculogenic function compared to endemic normals.